(untitled) (Fiep Bulletin - online, 2024)
Egypt was one of the first reports that mention swimming appeared in the year 5,000 BC and postural deviations are part of the daily life of a large part of the world’s adult population and it has been investigated whether they exist in individuals in the growth phase and how Swimming can help reverse these cases. Objective: The present work aims to differentiate postural deviations: kyphosis, lordosis and scoliosis and the influence of swimming on individuals’ body posture. Methods: The students at the Space Park academy in Feira de Santana were monitored, using observation, through which the supervising teacher was asked information about the students with postural deviations, the functional assessments carried out to carry out swimming, data regarding age, sex, weight, height. Results: the activities carried out during the internship were breathing, which teaches the student the technique of how to breathe when swimming; front crawl and backstroke, teaching the correct way of strokes, kicks, propulsion and breathing. Conclusión: Some scholars prove that swimming is the most suitable environment for reversing postural deviations. The action of physical properties causes a reduction in the impact on the spine, resulting in muscle relaxation.